Design and Simulation of Quasi-microstrip Yagi Antenna in Railway Mobile Communication - Shao, Junhua; Li, Qiang; Tan, Junmei (EAI Endorsed Transactions on Scalable Information Systems, 2025)
PROBLEM STATEMENT: The performance and size constraints of the current railway mobile communication systems force the development of more effective communication methods. OBJECTIVES: This study aims to build a quasi-microstrip Yagi antenna with a 900MHz centre frequency that minimizes the antenna’s physical dimensions and improves communication capabilities between trains. METHODS: HFSS simulation was used during the design phase to optimize the antenna’s characteristics, which included bending the active oscillator to increase gain. Important performance indicators were assessed, including voltage standing wave ratio (VSWR), bandwidth, and return loss. RESULTS: The optimized antenna produced a VSWR of less than 2, a maximum gain of 8.35dB, a bandwidth of 105MHz (spanning from 845MHz to 950MHz), and a return loss of -19.49dB at the centre frequency. According to these results, the antenna satisfies the operating criteria for railway mobile communication. CONCLUSION: The quasi-microstrip Yagi antenna proves useful in engineering applications since it not only meets the communication requirements of railway systems but also shrinks considerably in size compared to conventional Yagi antennas.